Changes in lipid and fatty acid contents of gonad during the reproductive cycle of the Mediterranean swordfish Xiphias gladius. (July 2022) - Sardenne, Fany; Millot, Remi; Bessis, Elodie; Puccinelli, Eleonora; Bideau, Antoine; Le Grand, Fabienne; Durieux, Éric Dominique Henri; Soudant, Philippe
Abstract: Swordfish Xiphias gladius is a large pelagic fish distributed worldwide and exploited for human consumption, however there is limited knowledge about its reproductive biology, especially regarding lipid dynamic in gonads. In teleost fish, reproductive success and offspring survival are associated to lipid availability for gamete synthesis. This study investigated the lipid composition, including lipid classes and fatty acids (FA) of cell membrane and reserve lipids (i.e., polar and neutral lipids, respectively; PL and NL), along female and male gonad development of a swordfish population from waters surrounding Corsica Island in the Mediterranean Sea. Overall, swordfish gonads contained <2% wet weight of total lipids, with testes and ovaries having similar fat content. Lipid classes and FA concentrations remained unchanged during testes maturation. However, concentrations of phosphatidyl choline (PL), triacylglycerol (NL), and some FA (16:0, 18:1n-9, and 22:6n-3) followed an "inverted U-shaped" relationship with the ovarian maturation. In both PL and NL, 22:6n-3 was the main polyunsaturated FA (>20% of total FA), while 20:5n-3 and 20:4n-6 were minor (3–6% of total FA) and varied little with maturation. 22:6n-3 and 18:1n-9 were selectively allocated to the ovarian maturation (increased in concentration and in proportion with maturation) until spawning. Finally, swordfish gonads might represent a good food source for humans given that 150 g of swordfish ovaries can cover the daily requirements in omega-3 for humans, but research on pollutants should also be conducted to evaluate their implications on the reproduction output of this species, and on the safety of swordfish gonads for human consumption. Highlights: Swordfish gonads contain <2% wet weight of total lipids. Triacylglycerol and phosphatidyl choline are two main lipid classes of swordfish gonad. Concentrations of the main lipid classes and FA increase in ovary until spawning. 22:6n-3 and 18:1n-9 are selectively allocated to the ovarian maturation until spawning. Swordfish gonad represents a valuable food source of omega-3 for humans.